use of encryption algorithms to secure NOSQL data in cloud databases the document data model - lassoued, rafika; ahmouda, chayma (universty of elouedجامعة الوادي, 2020)
أصبحت الحوسبة السحابية حلاً فعالاً لتخزين البيانات ، خاصة مع الحاجة المتزايدة لتوفير الموارد للتخزين وظهور ما يعرف بالبيانات الضخمة ، فهي أساس هندسة الحوسبة للجيل القادم من تكنولوجيا المعلومات (IT). نظرًا لأن التخزين السحابي هو نموذج للتخزين على الإنترنت ، حيث يتم تخزين البيانات على العديد من الخوادم المتعددة الموزعة على مراكز البيانات المتقدمة ، فإن الطبيعة غير الموثوقة للخوادم السحابية لا تزال تضع الباحثين وقادة هذه التقنية في مواجهة تحديات الأمان بالترتيب لضمان سرية البيانات المخزنة. الهدف الرئيسي من هذا العمل هو تنفيذ تقنية تشفير متجانسة تمامًا ، تسمح هذه التقنية بتوفير تشفير متماثل تمامًا وقابل للتكيف وفعال لتأمين بيانات NOSQL في قواعد البيانات السحابية Mongodb Atlas ، وهذا التشفير يسمح بتنفيذ العمليات على البيانات المشفرة المخزنة على مستوى السحابة بطريقة دقيقة وموثوقة.Cloud computing has become an effective solution for storing data, especially with the increasing need to provide resources for storage and the emergence of what is known as big data,it is the basis of computing engineering for the next generation of information technology (IT). Since cloud storage is a model for storage on the Internet, where the data is stored on many multiple servers distributed on advanced data centers, the untrusted nature of cloud servers remains still to put researchers and leaders of this technology in front of security challenges in order to ensure the confidentiality of the stored data. The main objective of this work is to implement a fully homomorphic encryption technology, this technology allows to provide a fully homomorphic, adaptable and efficient encryption to secure NOSQL data in Cloud databases Mongodb Atlas, this encryption allows the implementation of operations on the encrypted data stored at the cloud level in an accurate and reliable manner
mémouer de fin master informatique
Keywords: الكلمات الرئيسية - الحوسبة السحابية ، أمن الحوسبة السحابية ، تشفير متماثل تمامًا ، قاعدة بيانات NoSQL ، Mongodb.; Keywords— Cloud Computing, Cloud Computing security, fully homomorphic encryption, NoSQL database, Mongodb .